Crescimento, produção e qualidade do óleo essencial de Aloysia Triphylla em função da disponibilidade hídrica e sazonalidade - Prochnow, Daiane (2015)
Vegetative growth, and essential oil yield and its components are strongly influenced by photoperiod, temperature, rainfall, and other factors that change according to the seasonal period. Thus, this study aimed to evaluate the vegetative and productive and qualitative performance of Aloysia triphylla When subjected to different periods of drought during the four seasons. The experiment was conducted in an agroclimatology laboratory greenhouse at UFSM, campus of Frederico Westphalen RS. The experiment was conducted with a complete randomized block design in a 5x4 factorial scheme, the treatments consisting of five periods of water stress (3, 6, 9, 12 days without irrigation or daily irrigation) and four seasons (winter , spring, summer and fall); the study had five replications. The evaluations were performed in the period that marked the half of each season samples were collected throughout the growing material. Periods of drought did not affect the growth and essential oil production. Growth characters showed the highest values in the summer and autumn seasons, with the worst results in the winter. The highest essential oil content was obtained in the summer in all treatments and the lowest in the winter season. Citral is the major component of this oil, and it decreases in winter and increases in autumn and summer. The winter favors the concentration of minor components, especially caryophyllene oxide and spathulenol.